Effects of Increasing Exercise Intensity and Dose on Multiple Measures of HDL (High-Density Lipoprotein) Function. Issue 4 (April 2018) - Sarzynski, Mark A.; Ruiz-Ramie, Jonathan J.; Barber, Jacob L.; Slentz, Cris A.; Apolzan, John W.; McGarrah, Robert W.; Harris, Melissa N.; Church, Timothy S.; Borja, Mark S.; He, Yumin; Oda, Michael N.; Martin, Corby K.; et al.
Abstract : Objective—: Measures of HDL (high-density lipoprotein) function are associated with cardiovascular disease. However, the effects of regular exercise on these measures is largely unknown. Thus, we examined the effects of different doses of exercise on 3 measures of HDL function in 2 randomized clinical exercise trials. Approach and Results—: Radiolabeled and boron dipyrromethene difluoride–labeled cholesterol efflux capacity and HDL-apoA-I (apolipoprotein A-I) exchange were assessed before and after 6 months of exercise training in 2 cohorts: STRRIDE-PD (Studies of Targeted Risk Reduction Interventions through Defined Exercise, in individuals with Pre-Diabetes; n=106) and E-MECHANIC (Examination of Mechanisms of exercise-induced weight compensation; n=90). STRRIDE-PD participants completed 1 of 4 exercise interventions differing in amount and intensity. E-MECHANIC participants were randomized into 1 of 2 exercise groups (8 or 20 kcal/kg per week) or a control group. HDL-C significantly increased in the high-amount/vigorous-intensity group (3±5 mg/dL; P =0.02) of STRRIDE-PD, whereas no changes in HDL-C were observed in E-MECHANIC. In STRRIDE-PD, global radiolabeled efflux capacity significantly increased 6.2% (SEM, 0.06) in the high-amount/vigorous-intensity group compared with all other STRRIDE-PD groups (range, −2.4 to −8.4%; SEM, 0.06). In E-MECHANIC, non-ABCA1 (ATP-binding cassette transporter A1) radiolabeled efflux significantly increased 5.7% (95% CI, 1.2–10.2%) in the 20 kcal/kg per week group compared with the control group, with no change in the 8 kcal/kg per week group (2.6%; 95% CI, −1.4 to 6.7%). This association was attenuated when adjusting for change in HDL-C. Exercise training did not affect BODIPY-labeled cholesterol efflux capacity or HDL-apoA-I exchange in either study. Conclusions—: Regular prolonged vigorous exercise improves some but not all measures of HDL function. Future studies are warranted to investigate whether the effects of exercise on cardiovascular disease are mediated in part by improving HDL function. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifiers: NCT00962962 and NCT01264406. Abstract : Supplemental Digital Content is available in the text.